2020
DOI: 10.3389/fonc.2020.568069
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Imaging Quantification in Discriminating Non-Calcified Pulmonary Hamartoma From Adenocarcinoma

Abstract: Background: Patients with non-calcified hamartoma were more susceptible to surgery or needle biopsy for the tough discrimination from lung adenocarcinoma. Radiomics have the ability to quantify the lesion features and potentially improve disease diagnosis. Thus, this study aimed to discriminate non-calcified hamartoma from adenocarcinoma by employing imaging quantification and machine learning. Methods: Forty-two patients with non-calcified hamartoma and 49 patients with adenocarcinoma were retrospentation; Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 25 publications
2
8
1
Order By: Relevance
“…Radiomics involves using high-dimensional quantitative features extracted from imaging data to non-invasively quantify pathology. Recent studies have shown the potential for the application of radiomics in the oncological field [ 8 , 12 ]. This technique could complement the conventional approaches for analyzing the images and facilitate the process of delivering treatment tailored to individual patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Radiomics involves using high-dimensional quantitative features extracted from imaging data to non-invasively quantify pathology. Recent studies have shown the potential for the application of radiomics in the oncological field [ 8 , 12 ]. This technique could complement the conventional approaches for analyzing the images and facilitate the process of delivering treatment tailored to individual patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to extract multiple quantitative features from medical images, including CT and MRI, through the application of high-throughput computing [ 15 ]. These features include the use of intensity, shape, texture, wavelet, and LOG features to build predictive or prognostic non-invasive biomarkers for imaging modalities [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations